The Public Records Of The Colony Of Connecticut. Hartford, 1890 vol. 15 p. 191 - (:unkn) unknown (General Publisher, 1775)
Prohibited the exportation of salt petre, nitre, or gun powder out of the colony by land or water. Violators fined twenty pounds for every hundred weight of salt petre, nitre, or gun powder.
--
Keywords: GUN POWDER